2020
DOI: 10.1111/lasr.12471
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive Constitution-Making: Authoritarian Constitutionalism and the Military in Myanmar

Abstract: Constitutions are an important feature of many authoritarian regimes. But what role do they in fact perform in processes of authoritarian regime stabilization and legitimation? Much of the contemporary literature focuses on authoritarian constitutionalism in transitions away from constitutional democracy. This article considers the opposite scenario: pre‐emptive constitution‐making as a mechanism of authoritarian constitutionalism to contain a potential transition toward constitutional democracy. This is illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The border between authoritarian courts and democratic courts is blurry, and scholars gain by examining cases in the uncertain ranges. We have shown that the CCRK falls under the model of "authoritarian constitutionalism" (Trochev and Solomon 2018;Crouch 2020) or "autocratic legalism" (Scheppele 2018), and we focused our attention on the process by which judicial or quasi-judicial constitutional review bodies are captured and then leveraged to maintain these regimes. In Kazakhstan, that process produced a body that, over time, leveraged its authority over law to consistently reinforce the idea that the extended tenure of the president had constitutionally based legitimacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The border between authoritarian courts and democratic courts is blurry, and scholars gain by examining cases in the uncertain ranges. We have shown that the CCRK falls under the model of "authoritarian constitutionalism" (Trochev and Solomon 2018;Crouch 2020) or "autocratic legalism" (Scheppele 2018), and we focused our attention on the process by which judicial or quasi-judicial constitutional review bodies are captured and then leveraged to maintain these regimes. In Kazakhstan, that process produced a body that, over time, leveraged its authority over law to consistently reinforce the idea that the extended tenure of the president had constitutionally based legitimacy.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars focus specifically on democracies, including those democracies that are termed "new" or "nascent" (Ginsburg 2003;Chavez 2004). Others examine judiciaries under authoritarianism (Moustafa 2003(Moustafa , 2014Ginsburg and Moustafa 2008;Crouch 2020). Both sides of the split are interested in similar questions, such as the presence or absence of judicial independence, but they look at only one type of regime.…”
Section: Capturing Constitutional Reviewmentioning
confidence: 99%
“…Institutional loyalty is shaped by the political and legal environment in which the court exists. In the 1990s and 2000s, the military engaged in preemptive constitution-making, that is, it controlled the constitution-making process in order to contain a potential transition toward constitutional democracy (Crouch 2020). The purpose of preemptive constitution-making in authoritarian regimes is to use a new constitution to arrest and limit the possibility of transition, and ultimately to contribute to authoritarian-regime resilience.…”
Section: Case Study: the Militarization Of The Courts In Myanmarmentioning
confidence: 99%